La réalisation de garanties du fiduciaire et les syndiqués - Taschereau, Georges (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
In this article, the author discusses the application of sections 45 and 46 of the Quebec Labour Code in the context of the trust deed, at each step of the realization by the trustee of its securitees, namely : the taking of possession of the mortgaged assets and the carrying on of the operations of the debtor company by the trustee, as well as the acquisition or the taking charge of the mortgaged assets by a third party from the trustee. The author's argument or reasoning is based upon the unity of the two prerequisites for the application of section 45, i.e. a change of employer and the alienation or operation by another of the undertaking. On the basis of this reasoning, section 45 applies to the trustee who takes possession only when he deliberately carries on the undertaking of the debtor company, whether it be in whole or in part, or even for a limited time, because only then should the trustee be considered a new employer. The application of section 45 to a third party dealing with the trustee is also certain when such third party carries on the undertaking that the trustee had himself carried on. But the situation is not as certain when the trustee has not himself carried on the undertaking after taking possession, and the author explains the reasons for his doubts. Finally, in view of the current state of the law and jurisprudence, the author suggests alternate ways for the trustee to deal with a third party in order to avoid the application of section 45.